Teori Paulo Freire tentang Pendidikan sebagai Pembebasan dan Penerapan Metakognitif dalam Drama Korea Study Group (2025) - Rahma, Felinda; Syihabuddin,; Kembara, Maulia Depriya (Al-Riwayah : Jurnal Kependidikan, 2025)
This study explores how the ideas of education as liberation and metacognition are shown in the Korean drama Study Group (2025). The purpose of this research is to understand how the characters change the way they think and learn through reflection, teamwork, and self-awareness. The method used is qualitative content analysis by examining key scenes related to Paulo Freire’s theory and metacognitive strategies. The results show that the drama presents the struggles of students facing strong academic pressure in South Korea, but they grow through dialogical study groups. The characters learn to recognize their own strengths and weaknesses and develop appropriate learning strategies. In addition, Study Group serves as a critique of the Korean education system, which often emphasizes competition and individualism. This study concludes that Study Group illustrates how liberating and reflective education can help students become more independent, think critically, and support one another.